The Role of Participating in Team Sports Activities in Addressing Certain Behavioral Problems Among High School Students - Boudjellida, hassene (sports creativity, 2025)
The educational and instructional process gives significant importance to behavior and diligence when designing its curricula and developing its educational strategies, due to their importance in shaping humans and forming their personalities. Paying attention to behavioral issues is considered one of the main pillars of education, as its significance lies in the fact that education means a change in an individual’s behavior for the better under the influence of circumstances, experiences, knowledge, and skills that the student encounters in educational situations. Therefore, the impact of education is clearly reflected in the student’s positive behavior. If abnormal behavior appears in a student, it deserves study and research. Sports, as a social system and cultural complex, are part of the cultural fabric of society and individuals, and social values hold a prominent place in sports. Ethics, principles, and ideals extend in sports arenas just as they do in streets and markets, and can even be observed more intensely in the sporting field, as they are one of the educational and cultural forces in society. These ethics, values, principles, and sporting ideals did not arise from a specific situation or circumstance; rather, sports activities have been characterized by them and they have become an integral part of them. Many even say that the